Anti-Retroviral Treatment in dr. Sardjito Central General Hospital Yogyakarta - Labitta Pachira Aquaira; Sri Awalia Febriana; Nurwestu Rusetiyanti (Berkala Ilmu Kesehatan Kulit dan Kelamin (Periodical of Dermatology and Venerology))
Background: Adverse cutaneous drug reactions (ACDRs) affect 2-3% of hospitalized patients globally, wherein approximately 2% (1 in 1,000 cases) accounted for a severe form of cutaneous drug reactions. Out of all dermatologic diagnoses recorded by HIV patients, eight-point twenty-five percent of patients feature ACDRs, indicating that these patients are 100 times more inclined to develop unfortunate, severe reactions to anti-retroviral treatment. Therefore, there is an urgency in identifying the prevalence of ACDRs in HIV patients taking anti-retroviral treatment. Purpose: The aim of this study is to calculate the prevalence of anti-retroviral drug-induced ACDRs in HIV-positive patients in Central General Hospital, in the time period of January 2015 to December 2017. Methods: This study analyzed inpatient and outpatient medical records from January 2015 to December 2017 in the Dermatology and Venereology Department of dr. Sardjito Central General Hospital, which recorded ART-induced ACDRs manifestations. Result: This study revealed a prevalence of 0.095% of ACDRs as a result of ART administration, with 1.5% HIV-positive patients affected by ACDRs in response to ART medication. A m sex ratio of 2:1 with an average age of 30.4 ± 5.94 years old was found. The most predominant type of ACDR found in HIV-positive patients receiving ART was maculopapular rash (46.7%), while the most common type of drug within the ART regimen to cause such ACDR was Nevirapine (25.8%). Discussion: Nevirapine was the most common type of causative drug, for monotherapy (22.6%) and polytherapy (25.8%).